The labor market situation in Algeria between theory and reality - Berrima, Ali (Journal of Human Sciences, 2021)
This article discusses the labor market issue by analyzing and clarifying the different dimensions related to it, in terms of relation with education and its products, as well as the different theoretical concepts related to this concept, as well as the situation of the labor market in Algeria and its historical evolution. The descriptive-analytical approach and the historical approach have been used to address this issue methodologically. We conclude that labor market trends and educational patterns vary due to many variables. For this reason, planners plan educational policies in response to changes in the labor market by reviewing educational programs in light of socio-cultural and technological developments in society.